2000
DOI: 10.1159/000012082
|View full text |Cite
|
Sign up to set email alerts
|

Second Malignancies following Pure Seminoma

Abstract: Purpose: Second malignancies in patients with pure testicular seminoma were studied in order to look for adverse late effects of treatment and to study the significance of second malignancies during follow-up. Patients, Methods: In a multicentric investigation, 839 consecutive patients with pure testicular seminoma were observed for a median follow-up of 3.9 years. Thirty-seven patients had been excluded from the study because they already had had either a contralateral testicular germ cell tumor or another ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…These studies, whilst instructive for specific populations, should not necessarily be used to estimate risk for patients without malignant disease. This is highlighted by the fact that some of these tumours occur with increasing frequency at nonirradiated sites and are therefore due to factors unrelated to treatment-possibly genetic pre-disposition [10]. After treatment for benign disease such as Grave's ophthalmopathy in young patients, an absolute lifetime risk of radiation-induced cancer has been estimated at 0.3% [3].…”
Section: Discussionmentioning
confidence: 99%
“…These studies, whilst instructive for specific populations, should not necessarily be used to estimate risk for patients without malignant disease. This is highlighted by the fact that some of these tumours occur with increasing frequency at nonirradiated sites and are therefore due to factors unrelated to treatment-possibly genetic pre-disposition [10]. After treatment for benign disease such as Grave's ophthalmopathy in young patients, an absolute lifetime risk of radiation-induced cancer has been estimated at 0.3% [3].…”
Section: Discussionmentioning
confidence: 99%
“…2 Reports of ureteral cancer in patients with testicular seminoma are rare. 9 However, some investigators have reported elevated risks of cancer of the bladder and the kidney among such patients. 2,9 Travis et al 2 found that urothelial carcinoma of the renal pelvis (n = 20) accounted for approximately 33% of kidney cancers for which the histologic type was specifi ed (n = 61); this is more frequent than the incidence in the general population (approximately 10% of all renal tumors).…”
Section: Discussionmentioning
confidence: 99%
“…Rüther et al [7 ]observed an increased risk of second malignancy after seminoma therapy by irradiation to the PA and ipsilateral pelvic nodes at doses of 26–36 Gy. The risk of renal cell cancer was significantly increased, while that of rectal cancer and non-Hodgkin’s lymphoma was increased but not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…A cure is also achieved in nearly 100% of these patients by subsequent salvage chemotherapy. Contralateral germ cell tumors occur in 1.5% of the cases and are usually metachronous [7]. …”
Section: Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation